Genomics-Assisted Crop Improvement
DOI: 10.1007/978-1-4020-6297-1_10
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetics and Breeding of Grain Legume Crops for the Semi-Arid Tropics

Abstract: Grain legumes are important crops for providing key components in the diets of resource-poor people of the semi-arid tropic (SAT) regions of the world. Although there are several grain legume crops grown in SAT, the present chapter deals with three important legumes i.e. groundnut or peanut (Arachis hypogaea), chickpea (Cicer arietinum) and pigeonpea (Cajanus cajan). Production of these legume crops are challenged by serious abiotic stresses e.g. drought, salinity as well as several fungal, viral and nematode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
1

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 156 publications
(162 reference statements)
1
52
1
Order By: Relevance
“…Genomic DNA was extracted from the young leaf tissues of 2-week-old seedlings using the modified method described by Dellaporta et al (1983). Nineteen polymorphic SSRs were used for genotyping, from the available composite collections of International Crops Research Institute for the Semi-Arid-Tropics (ICRISAT) and International Center for Agricultural Research in the Dry Areas (ICARDA) (Varshney et al, 2007). Among them, 12 trinucleotide repeat motifs markers of 113-496 bp allele size with annealing temperature of 56-59°C (Winter et al, 1999), and 4 di-nucleotide repeat motifs markers of 201-464 bp allele size with annealing temperature of 56°C (Sethy et al, 2003) showed polymorphism.…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA was extracted from the young leaf tissues of 2-week-old seedlings using the modified method described by Dellaporta et al (1983). Nineteen polymorphic SSRs were used for genotyping, from the available composite collections of International Crops Research Institute for the Semi-Arid-Tropics (ICRISAT) and International Center for Agricultural Research in the Dry Areas (ICARDA) (Varshney et al, 2007). Among them, 12 trinucleotide repeat motifs markers of 113-496 bp allele size with annealing temperature of 56-59°C (Winter et al, 1999), and 4 di-nucleotide repeat motifs markers of 201-464 bp allele size with annealing temperature of 56°C (Sethy et al, 2003) showed polymorphism.…”
Section: Methodsmentioning
confidence: 99%
“…Important pre-requisites for undertaking molecular breeding are molecular markers, genetic maps and markers associated with traits [42]. Isozyme markers were used for map development in chickpea during the early days of genomic studies.…”
Section: Development Of Molecular Markersmentioning
confidence: 99%
“…Molecular markers have become indispensable tools in genomics-assisted breeding (Varshney et al 2007) for crop improvement. Among several kinds of molecular markers, the simple sequence repeat (SSR) markers are considered as the markers of choice owing to high reproducibility and co-dominant nature (Gupta and Varshney 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Among several kinds of molecular markers, the simple sequence repeat (SSR) markers are considered as the markers of choice owing to high reproducibility and co-dominant nature (Gupta and Varshney 2000). Further, genic SSRs (derived from cDNA/expressed sequence tags (ESTs) are, more robust for gene discovery and to study variation in transcribed regions and genes of known-function, very useful in plant genome analysis and crop improvement (Varshney et al 2005(Varshney et al , 2007. In addition, genic SSRs derived from ESTs with homology to candidate genes are good targets for genetic mapping and aligning genome linkage maps across distantly related species for comparative analysis (Holton et al 2002).…”
Section: Introductionmentioning
confidence: 99%